“What is the Citie, but the People? True, the People are the Citie.” Coriolanus, Act III., Sc. I. - Ladislav Vít (American and British Studies Annual, 2010)
Review of: The Postmodern City of Dreadful Night: The image of the city in the works of Martin Amis and Ian McEwan by Peter Chalupský (Saarbrücken: VDM Verlag, 2009. 133 pp. ISBN 978-3-639-14446-8).